Ocular biomarkers and their role in the early diagnosis of neurocognitive disorders. Issue 6 (November 2021) - Chalkias, Ioannis-Nikolaos; Tegos, Thomas; Topouzis, Fotis; Tsolaki, Magda
Given the fact that different types of dementia can be diagnosed only postmortem or when the disease has progressed enough to cause irreversible damage to certain brain areas, there has been an increasing need for the development of sensitive and reliable methods that can detect early preclinical forms of dementia, before the symptoms have even appeared. Ideally, such a method would have the following characteristics: to be inexpensive, sensitive and specific, Non-invasive, fast and easily accessible. The ophthalmologic examination and especially the study of the retina, has caught the attention of many researchers, as it can provide a lot of information about the CNS and it fulfills many of the aforementioned criteria. Since the introduction of the non-invasive optical coherence tomography (OCT) and the newly developed modality OCT-angiography (OCT-A) that can demonstrate the structure and the microvasculature of the retina and choroid, respectively, there have been promising results regarding the value of the ophthalmologic examination in the early diagnosis of Alzheimer's disease. In this review paper, we summarize and discuss the ocular findings in patients with cognitive impairment disorders and we highlight the importance of the ophthalmologic examination to the diagnosis of these disorders.